2001
DOI: 10.1037/0735-7028.32.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning and accessing new roles for professional psychology.

Abstract: To support psychology's continued evolution as a profession, it is important to conceptualize roles that psychologists can play in the future and create pathways for developing and accessing them. This article considers a variety of roles that may become central to professional psychology in the future. Important opportunities appear to exist in the areas of psychological management of health and disease, serious mental illness, and public policy. Psychology faces both internal and external barriers to accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…APA could provide leadership in helping state PRNs to organize, facilitating meetings among state PRNs, providing consultations for assessment and design issues, and contributing to the organization and management of a national database. It is noteworthy that the final report of an APA task force (Levant et al, 1999) on envisioning, identifying, and accessing new professional roles specifically recommended that “we seek ways to encourage scientists to work with practitioners to improve the documentation of long‐term effectiveness of our interventions across the range of practice settings… . One model for this may be the practice research network, such as the one that has been launched by the Pennsylvania Psychological Association” (p. 18).…”
Section: Discussionmentioning
confidence: 99%
“…APA could provide leadership in helping state PRNs to organize, facilitating meetings among state PRNs, providing consultations for assessment and design issues, and contributing to the organization and management of a national database. It is noteworthy that the final report of an APA task force (Levant et al, 1999) on envisioning, identifying, and accessing new professional roles specifically recommended that “we seek ways to encourage scientists to work with practitioners to improve the documentation of long‐term effectiveness of our interventions across the range of practice settings… . One model for this may be the practice research network, such as the one that has been launched by the Pennsylvania Psychological Association” (p. 18).…”
Section: Discussionmentioning
confidence: 99%
“…These include developing and conducting functional assessments; studying the reliability and validity of diagnostic categories; developing illness management and behavioral techniques to reduce stress and increase medication adherence, coping and educational programs; and developing, implementing, and evaluating EBPs (many of these contributions are summarized in Smith et al, 1993). Despite these important achievements and the fact that several single psychologists have made major contributions to this emerging field (often referred to as psychiatric rehabilitation), most agree that only a small proportion of clinical psychologists choose and work with persons with SMI (Levant et al, 2001; Rollins & Bond, 2001). Supporting this view are national survey findings.…”
Section: Introduction: the Underrepresentation Of Clinical Psychologimentioning
confidence: 99%
“…In 1960, approximately half of all psychologists worked in CMH clinics and hospitals (Norcross, Karpiak, & Santoro, 2005). In contrast, current data indicate that professional psychologists are underrepresented in the public sector (Levant et al, 2001;Reddy et al, 2010;Roe et al, 2006;Shore, 1992). APA's, 2010 demographics showed that only .3% of Division 12 (clinical psychology), .7% of Division 17 (counseling psychology), and .1% of Division 16 (school psychologists) associates, members, and fellows identified as community psychologists (APA Center for Workforce Studies, 2010).…”
Section: Psychology's Decline Of Representation In Public Psychologymentioning
confidence: 98%